2020
DOI: 10.1016/j.pedn.2019.09.023
|View full text |Cite
|
Sign up to set email alerts
|

Global Pediatric Peripheral Intravenous Catheter Practice and Performance: A Secondary Analysis of 4206 Catheters

Abstract: To describe worldwide characteristics, performance and risk factors of peripheral intravenous catheters (PIVCs), in pediatrics. Design: A secondary, subgroup analysis of pediatric (b18 years) data was undertaken, using a global, crosssectional study of PIVCs. Practice characteristics included: demographic, diagnostic, utility, management, performance and resources. Multivariate regression identified complication risks factors. Results: Data from 4206 children in 278 hospitals across 47 countries. Most PIVCs (o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
54
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 57 publications
(61 citation statements)
references
References 33 publications
2
54
0
5
Order By: Relevance
“…Peripheral intravenous catheter (PIVC) insertion is one of the most common procedures in hospitalized children (Ben Abdelaziz et al, 2017;Marsh, Webster, Mihala, & Rickard, 2015;Ullman et al, 2020). PIVC insertion is frequently challenging in children and insertion attempts requiring 10 or more attempts are reported (Cooke et al, 2018;Kleidon et al, 2017;Ullman et al, 2020). A cross-sectional study conducted in 25 countries evaluated PIVC placements in children.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Peripheral intravenous catheter (PIVC) insertion is one of the most common procedures in hospitalized children (Ben Abdelaziz et al, 2017;Marsh, Webster, Mihala, & Rickard, 2015;Ullman et al, 2020). PIVC insertion is frequently challenging in children and insertion attempts requiring 10 or more attempts are reported (Cooke et al, 2018;Kleidon et al, 2017;Ullman et al, 2020). A cross-sectional study conducted in 25 countries evaluated PIVC placements in children.…”
Section: Introductionmentioning
confidence: 99%
“…An international study evaluating use of PIVCs (n = 40,620) in 51 countries found catheter placement in non-recommended sites (66%), idle PIVCs (14%), pain on assessment (10%), symptoms of phlebitis (10%) and suboptimal dressings (21%) (Alexandrou et al, 2018). A study evaluating global pediatric PIVC practices in 47 countries (including Africa) found numerous inconsistencies in PIVC care (Ullman et al, 2020). This secondary data analysis of 4206 PIVCs revealed the need for improved catheter placement, consistent PIVC observation and assessment, removal of idol PIVCs, and focus on dressing integrity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Less than half of the respondents reported having 24/7 coverage for vascular access coverage, with a recent global study identifying pediatric vascular access specialist teams being most common in the US. 11 For those who answered that they did not have a vascular access team, vascular access is provided by the bedside RN in most of the responses.…”
Section: Procedural Supportmentioning
confidence: 99%
“…An international research study ( 3 ) conducted with children from 278 hospitals in 47 countries in Africa, Asia, Australia/New Zealand, Europe, the Middle East, North America, South America and the South Pacific, demonstrated that, in 11.4% of the catheter insertion sites, signs of some complication were observed, while the incidence of these events was estimated at 18.6% in a prospective longitudinal study carried out in Bahia, Brazil ( 4 ) .…”
Section: Introductionmentioning
confidence: 99%